Analisis Potensi Wisata Desa Wisata Tarabunga, Kabupaten Toba, Sumatera Utara - Tuan Bobby Harsono Sinaga; Hanif Hasan (Jurnal Visi Manajemen, 2025)
Tourism is one of the largest sources of income in many developed and developing countries, especially in Indonesia. Tarabunga Village, which is in Toba Regency, North Sumatra, currently does not seem to receive optimal attention. This research was conducted to analyze the tourism potential of the Tarabunga Tourism Village using qualitative research methods with parameters that can be measured from the 6A theory (attractions, activities, accessibility, amenities, additional services and available tour packages), then using observation, interviews, and other techniques. and questionnaires, as well as using SWOT analysis techniques to answer the strategy for developing the tourism potential of Tarabunga Tourism Village.